2019
DOI: 10.1097/ju.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiation Therapy for Localized Prostate Cancer: Executive Summary of an ASTRO, ASCO and AUA Evidence-Based Guideline

Abstract: The aim of this guideline is to present recommendations regarding moderately hypofractionated (240-340 cGy per fraction) and ultrahypofractionated (500 cGy or more per fraction) radiation therapy for localized prostate cancer. Methods and Materials: The American Society for Radiation Oncology convened a task force to address 8 key questions on appropriate indications and dosefractionation for moderately and ultrahypofractionated radiation therapy, as well as technical issues, including normal tissue dose const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 6 publications
(6 reference statements)
2
86
0
3
Order By: Relevance
“…Treatments with low doses per fraction could be used to reduce the overall effect of large dose hotspots in the rectal wall. Ultra‐hypofractionated treatments using large doses per fraction could be prohibited, or replanned if unplanned gas is detected during daily imaging …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments with low doses per fraction could be used to reduce the overall effect of large dose hotspots in the rectal wall. Ultra‐hypofractionated treatments using large doses per fraction could be prohibited, or replanned if unplanned gas is detected during daily imaging …”
Section: Discussionmentioning
confidence: 99%
“…All simulations were prescribed 4 Gy to the isocenter, using 1% statistical uncertainty, 0.1‐cm grid spacing, and an MR‐Linac‐specific beam model. The 4‐Gy dose prescription was chosen in line with the various conventional External Beam Radiotherapy (EBRT; 1.8–2 Gy), moderately hypofractionated (2.4–3.4 Gy), and ultra‐hypofractionated (>5–7.25 Gy) prostate dose prescriptions and treatment schedules …”
Section: Methodsmentioning
confidence: 99%
“…Hypofractionation — both moderate and stereotactic‐level — was also not addressed but has since become standard of care for several of the most commonly treated organ sites. ASTRO guidelines for hypofractionated or stereotactic treatment have published within past 2 yr for lung, prostate, and breast cancer . Since QUANTEC, there have been similar efforts by PENTEC (Pediatric Normal Tissue Effects in the Clinic) and the AAPM working group HyTEC (Hypofractionation Treatment Effects in the Clinic) to determine normal tissue effects for pediatric patients and hypofractionated regimens, respectively.…”
Section: Normal Tissue Radiosensitivitymentioning
confidence: 99%
“…Based on these large trials, as well as additional single‐institution randomized trials, hypofractionated EBRT guidelines were published collaboratively by the American Society of Clinical Oncology, the American Urological Association and the American Society for Radiation Oncology . In these guidelines, it is concluded that patients treated with moderate hypofractionation (2.4–3.4 Gy per fraction) might have a small increased risk of acute GI toxicity, and have a similar risk of acute and late GU and late GI toxicity compared with conventionally fractionated EBRT, although it should be noted that these data were based on most randomized trials with limited follow up beyond 5 years.…”
Section: Hypofractionated Radiotherapymentioning
confidence: 99%
“…Clinicians should keep in mind that an increase of just 1.25 Gy in total dose has tended to increase toxicity. Therefore, in the guidelines mentioned above, although ultrahypofractionation might be offered as an alternative to conventional fractionation in men with low‐risk prostate cancer, ultrahypofractionation for patients with intermediate‐ or high‐risk prostate cancer should be used as part of a clinical trial or multi‐institutional registry due to the possible risk of late toxicity . The support of clinical trials or multi‐institutional registries is required to firmly assess the efficacy and toxicity of ultrahypofractionated EBRT.…”
Section: Hypofractionated Radiotherapymentioning
confidence: 99%